Comparison of the vertical jump performance of footballers with cerebral palsy at different competitive levels - Matías Henríquez; Kevin Campos-Campos; Raúl Smith; Sebastián Aliste; Sonny Riquelme; Raul Reina (European Federation of Adapted Physical Activity, 2023)
Vertical jump (VJ) capacity is a common assessment for monitoring athletes' neuromuscular function and has been proposed as a differentiating indicator between competitive levels of football players. This study aimed to compare the VJ capacity of Chilean footballers with cerebral palsy (CP) with international and national levels of proficiency, also according to their sport classes (i.e., FT1‒FT3). A total sample of 41 male footballers with CP were divided into international-level (n = 18) and national-level (n = 23) groups. All the participants performed two maximal squat jumps (SJs) and countermovement jumps (CMJs), where the best height obtained was registered. The VJ performance was significantly different between competitive levels, and players at international level had better scores (p < .001) than the national level in SJ (dg = 1.83, large) and CMJ (dg = 2.08, large). Considering the sport classes, significant differences were found in SJ (p = .024) and CMJ (p = .035), in which FT3 players performed higher jumping heights than FT1 players (dg = -.84 to -1.01, large). These results provide a deeper understanding of the differences in the motor impairment-specific performance of para-footballers with CP, where coaches and strength-conditioning professionals should consider VJ assessment for monitoring training and as a component for talent detection in this para-sport.